The Great Recession and the Inflation Puzzle - Matheson, Troy.; Stavrev, Emil. (Washington, D.C. : International Monetary Fund, 2013)
Notwithstanding persistently-high unemployment following the Great Recession, inflation in the United States has been remarkably stable. We find that a traditional Phillips curve describes the behavior of inflation reasonably well since the 1960s. Using a non-linear Kalman filter that allows for time-varying parameters, we find that three factors have contributed to the observed stability of inflation: inflation expectations have become better anchored and to a lower level; the slope of the Phillips curve has flattened; and the importance of import-price inflation has increased.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet